Repositioning nystagmus: prognostic usefulness?. (May 2014) - Marques, Pedro Santos; Castillo, Rosa; Santos, Margarida; Perez-Fernandez, Nicolas
Abstract Conclusions: The presence of orthotropic nystagmus (ON), in multiple positions, appears to predict the success of canalith repositioning maneuvers (CRMs). In this sense CRMs under video-Frenzel are informative for the immediate follow-up, although not related to the degree of disability or emotional distress. Still, attention should be given to psychological assistance even in cases of clinically cured benign paroxysmal positional vertigo (BPPV). Objective: The aim of the study was to highlight the prognostic value of nystagmus in CRMs for BPPV and its relevance for emotional and patient-perceived disability. Methods: A group of 57 patients were selected from 3 balance disorders centers. CRMs were performed under video-Frenzel control. Assessment of patient disability and positional nystagmus was performed 2 months later. Emotional (Cuestionario de Impacto Emocional del Vértigo, CIEV) and quality of life (Dizziness Handicap Inventory, DHI) impact were evaluated. Results: The posterior semicircular canal (SCC) was affected in 84.2% of cases, the horizontal SCC in 10.5%, and the anterior SCC in 5.1%. Appropriate CRMs were performed. ON was present in 67% of cases. Overall resolution after the first treatment was achieved in 56% of cases. With ON present the success rate was 63% and when not observed the rate was 42%. DHI or CIEV scores were not significantly different when comparing the presence vs absence of ON. In nine patients (16%) an abnormal CIEV score was observed after treatment, even though a cured status was achieved in six of these nine patients.